2021
DOI: 10.3389/fphys.2021.562817
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Analysis of Chicken Anterior Pituitary: A Bird’s-Eye View on Vertebrate Pituitary

Abstract: It is well-established that anterior pituitary contains multiple endocrine cell populations, and each of them can secrete one/two hormone(s) to regulate vital physiological processes of vertebrates. However, the gene expression profiles of each pituitary cell population remains poorly characterized in most vertebrate groups. Here we analyzed the transcriptome of each cell population in adult chicken anterior pituitaries using single-cell RNA sequencing technology. The results showed that: (1) four out of five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 112 publications
(209 reference statements)
0
16
0
Order By: Relevance
“…RLN3 is highly expressed in female pituitary gonadotrophs but not in male pituitary gonadotrophs. Similarly, GRP , HPGDS , and CPLX1 have relatively higher mRNA levels in female than that in male gonadotrophs, which was confirmed by using quantitative real-time PCR (qPCR) to indicate the sexually dimorphic expression patterns of GRP , RLN3 , and HPGDS at the whole anterior pituitary level (Zhang et al, 2021). In addition, some novel differentially expressed genes were revealed in this study.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…RLN3 is highly expressed in female pituitary gonadotrophs but not in male pituitary gonadotrophs. Similarly, GRP , HPGDS , and CPLX1 have relatively higher mRNA levels in female than that in male gonadotrophs, which was confirmed by using quantitative real-time PCR (qPCR) to indicate the sexually dimorphic expression patterns of GRP , RLN3 , and HPGDS at the whole anterior pituitary level (Zhang et al, 2021). In addition, some novel differentially expressed genes were revealed in this study.…”
Section: Resultsmentioning
confidence: 75%
“…In the chicken pituitary, some genes with a high TPM value (>200) are expressed in a sex-dependent manner, including LOC121107016 , LOC121107017 , LOC112533599 , CPLX1 , RLN3 , GRP , HPGDS , HEXB , SPARCL1 in female, and HSPA5 , PLK2 , CSRP2 , CCDC80 , LOC112532140 , MEM201 in male (Figure 6E). Interestingly, in our previous scRNA-seq study, we found that in gonadotrophs clusters of the chicken anterior pituitary, some genes ( CPLX1 , RLN3 , GRP and HPGDS ) are also expressed in a sex-dependent manner (Zhang et al, 2021). RLN3 is highly expressed in female pituitary gonadotrophs but not in male pituitary gonadotrophs.…”
Section: Resultsmentioning
confidence: 90%
“…Especially, the mouse CRHBP is detected to be highly expressed in the pituitary gland with a sexually dimorphic pattern, with females exhibiting much higher expression levels [ 30 , 50 ]. Single-cell sequencing from our research group further reveals that chicken CRHBP is abundantly expressed in pituitary folliculostellate cells (FS cells) [ 51 ], being different from the detection in female mice that CRHBP is expressed in pituitary cells, including corticotropes, lactotropes and gonadotropes [ 30 ]. The FS cells in the chicken pituitary are hypothesized to function as a paracrine/autocrine signaling hub, influencing neighboring cells [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…cDNA samples were subjected to quantitative real-time PCR assay of chicken MC5R mRNA levels in different chicken tissues, as described in our previous study ( Fang et al, 2021 ; Zhang et al, 2021 ). Quantitative real-time PCR (qPCR) was performed on the CFX96 Real-time PCR Detection System (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%